Disruptive effects of phthalates and their substitutes on adrenal steroidogenesis - Pötzl, Benedikt; Kurlbaum, Max; Kendl, Sabine; Kürzinger, Lydia; Herterich, Sabine; Kloock, Simon; Fassnacht, Martin; Dischinger, Ulrich (Frontiers in Endocrinology, 2026)
IntroductionPhthalates are ubiquitous plasticizers known for their endocrine-disrupting properties, notably affecting reproductive and cardiovascular health. Emerging substitutes such as DEHT and DINCH are increasingly use, but may turn out to be “regrettable substitutes” with similar toxicological concerns. Though the effects of phthalates and substitutes on adrenal steroidogenesis and related endocrine systems (e.g., renin-angiotensin-aldosterone system, hypothalamic-pituitary axis) remain poorly understood.MethodsIn this study, steroidogenic NCI-H295R adrenocortical cells were exposed for 72 hours to phthalates (DEHP, DiBP, DiNP), substitutes (DEHA, DEHT, DINCH), and a cumulative mixture at concentrations ranging from 1 nM to 1 mM. DMSO vehicle controls were included in all experiments. Cytotoxicity was assessed using standard cell viability assays, while steroid secretion was quantified by LC–MS/MS, covering 15 adrenal steroids. Relative enzymatic activities were estimated from steroid ratios. mRNA expression of key molecules involved in adrenocortical steroidogenesis was analyzed by RT-qPCR.ResultsCortisol, 21-deoxycortisol, corticosterone, and aldosterone were significantly increased after treatment with DEHP, DiNP, DEHT, DINCH, and their combinatory mixture at non-cytotoxic doses (e.g., corticosterone 6.51-fold increase at 5 µM DEHP). Phthalates and substitutes dysregulated steroidogenic enzyme activity, notably inhibiting HSD11B2’s conversion of cortisol to cortisone below 25% in relation to controls. Combinatory exposure led to an increased mRNA expression of CYP11B1 (11.8-fold at 10 µM) and CYP11B2 (44.1-fold at 10 µM) as well as other steroidogenic enzymes (e.g., CYP21A2, HSD3B2) and key adrenocortical receptors (e.g., MC2R, AGTR1) when compared to untreated controls.DiscussionThis in vitro study provides novel evidence on phthalate- and substitute-induced endocrine disruption of adrenal steroidogenesis, favouring mineralo- and glucocorticoid secretion, potentially linking these substances to secondary hypertension. Notably, emerging substitute substances (e.g., DEHT, DINCH) showed similar effects of adrenal disruption, compared to classical phthalates.